Avaliação do potencial de geração de energia eólica no Rio Grande do Sul : mapas de calor de velocidade do vento e cálculo de potência de turbinas - Silva, Vinicius Amaro Ferreira da (2024)
Due to growing awareness of the use and availability of energy resources worldwide, technological evolution is moving toward a scenario where all electricity used is expected to originate from renewable energy sources. Consequently, this scenario has triggered a race for technologies to dominate the energy generation market with minimal pollution, delivering results in record time through new methods of conversion and utilization of diverse energy sources. Therefore, it is essential to study the feasibility of implementing these new sources in different regions, aiming to expand energy generation with new projects and diverse deployment methods. In the case of wind energy, the primary step is studying the location concerning the wind speed available for generation, which may involve various techniques. This is one of the most critical stages for successful energy generation. Given the variations in wind speed by region and height, multiple viable energy production scenarios may exist at a single site designated for a wind project, necessitating studies to determine the best generation scenario. The annual energy production is intrinsically linked to the installation site of the wind turbine, encompassing factors that influence the speed the turbine can harness and the power it can generate over time. With this in mind, the present study aims to demonstrate how variations in wind speed at different heights can drastically impact the power available for wind turbines and the annual energy generation in different scenarios. Using data from Rio Grande do Sul, heat maps illustrate the potential contexts to consider when making decisions based on wind speed variation. Utilizing wind speed data available on platforms, heat maps were generated for the available heights, and the power corresponding to wind speeds was calculated for different scenarios. With example turbine power, it is possible to calculate the annual energy generation based on the frequency of wind speed occurrences. The study proved useful for specific generation analyses tailored to scenarios of interest, focusing on particular study regions.